Vietnam's Post‐Cold War Hedging Strategy: A Changing Mix of Realist and Liberal Ingredients. Issue 1 (29th January 2018) - Tran, Thi Bich; Sato, Yoichiro
Abstract : This article aims at improving precision in the theoretical discussions of "hedging" strategy. It proposes a generalizable basket of the strategy's components. It then examines the evolution of Vietnam's hedging strategy since the end of the Cold War based on this framework. The findings show that Vietnam's hedging strategy is a dynamically changing mix of four realist and liberal ingredients (diplomatic engagement, economic engagement, soft balancing, and hard balancing). The most dominant component in Vietnam's hedging has shifted across different periods, as Vietnam reacted to China's movements in the South China Sea as well as changes in the domestic conditions and the external security environment.